2016
DOI: 10.1016/j.kjms.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Significance of preoperative neutrophil–lymphocyte count ratio on predicting postoperative sepsis after percutaneous nephrolithotomy

Abstract: We evaluated the usefulness of preoperative neutrophil-lymphocyte count ratio (NLCR) in predicting postoperative sepsis after percutaneous nephrolithotomy (PCNL). In total, 487 patients who underwent PCNL for renal stones were included in the present retrospective study. The stone burden, number of tracts and location, operation time, fluoroscopy time, presence of residual stones, and blood transfusion rates were postoperatively recorded in all patients. All patients were followed up for signs of systemic infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 32 publications
6
26
1
1
Order By: Relevance
“…A total of 30.1% of patients developed SIRS, and no patients developed sepsis. Current studies have shown that the incidence of SIRS after PCNL is between 10% and 30% (6,14). This value was similar to the results in the literature (15, 16) but higher than those in the studies of Wang A]QL (12.5%) and Singh P (17.5%) (3,9).…”
Section: Discussionsupporting
confidence: 87%
“…A total of 30.1% of patients developed SIRS, and no patients developed sepsis. Current studies have shown that the incidence of SIRS after PCNL is between 10% and 30% (6,14). This value was similar to the results in the literature (15, 16) but higher than those in the studies of Wang A]QL (12.5%) and Singh P (17.5%) (3,9).…”
Section: Discussionsupporting
confidence: 87%
“…According to the results of our study, 97% of patients without postoperative fever can be estimated by considering NLR and lymphocyte count. We think that postoperative fever and bacteremia can be prevented by various antibiotic prophylaxis strategies and therapeutic (22) demonstrated that the NLR after post-PCNL septicemia was an independent factor in multivariate analysis with a threshold value which is close to the one in our study (>2.5). We think that the reason as to why the NLR value in our study was not significant in the multivariate analysis was the varying number of patients in the two groups (469 vs 50).…”
Section: Discussionsupporting
confidence: 79%
“…Sonuç: PNL yapılan hastalarda ateş oluşturabilecek risk faktörleri dışladığında lenfosit sayısı ve NLO postoperatif ateşi öngörmede kullanılabilecek kolay ve ucuz bir tanı aracı olarak gözükmektedir. Anahtar Kelimeler: Bakteriyemi, Ateş, PNL, Nötrofil-lenfosit oranı Journal of Urological Surgery, 2020;7(1): [21][22][23][24][25][26] was used to compare non-parametric variables. A p value of less than 0.05 was considered statistically significant.…”
Section: Discussionunclassified
“…CRP was measured using the BCG dye‐binding method and a turbidimetric assay; the normal range at our institution was 0–10 mg/L. The stone burden was calculated by multiplying the longest diameter by the perpendicular diameter of the stone, and the sum of each stone as the total stone burden in cases of multiple stones [8].…”
Section: Methodsmentioning
confidence: 99%